Analisis Klaim Rawat Inap RSUD Kebayoran Baru November 2022 – April 2023: Pendekatan Sistem - Rabiulyati, May; Nurwahyuni, Atik; Pujiyanto, Pujiyanto (UI Scholars Hub, 2024)
Hospitals receive payments through claim submissions with complete documents to the Social Security Administering Agency (BPJS) Health. However, not all inpatient claims have been submitted to BPJS Health, and there are still 16.97% pending inpatient claims. In claims that are not approved, claims can be resubmitted, but time constraints for the claim process have resulted in 2.64% of inpatient cases in 2022 not resubmitted. Qualitative research through in-depth interviews with 15 respondents aims to analyze the management of inpatient claims for BPJS Kesehatan Kebayoran Baru Hospital from November 2022 to April 2023. The study results showed that not all printed Participant Eligibility Letters (SEP) have been submitted for inpatient claims. There were 10.97% pending claims, with the cause being incomplete doctor's medical resumes for 59 inpatient files (32.2%) and inconsistencies in submitting claim files for 81 inpatient files (44.3%). This is due to the suboptimal feedback and monitoring, so it is necessary to establish a claim management monitoring flow. Hospitals must also establish Standard Operating Procedures (SOP) for integrated claim management. This study is expected to be a strategic guide to improve BPJS Kesehatan claim management with Focus Group Discussion (FGD) efforts for collaboration between agencies/units/teams and better cooperation between hospitals and BPJS Kesehatan. All solutions implemented are expected to improve the quality of hospital claims.